2018
DOI: 10.1039/c7ra12499f
|View full text |Cite
|
Sign up to set email alerts
|

Dimeric cinchona ammonium salts with benzophenone linkers: enantioselective phase transfer catalysts for the synthesis of α-amino acids

Abstract: Novel cinchona-alkaloid derived dimeric phase transfer catalysts (PTC) with benzophenone linkers and their α-alkylation of glycinate esters has been presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Bis(4-(bromomethyl)phenyl)methane and bis(4-(bromomethyl)phenyl)methanone were prepared by following known procedures. 15 ATR-IR spectra were recorded on a Nicolet iS5 IR spectrophotometer. NMR spectra were recorded on a Bruker Avance III 500 MHz spectrometer.…”
Section: Methodsmentioning
confidence: 99%
“…Bis(4-(bromomethyl)phenyl)methane and bis(4-(bromomethyl)phenyl)methanone were prepared by following known procedures. 15 ATR-IR spectra were recorded on a Nicolet iS5 IR spectrophotometer. NMR spectra were recorded on a Bruker Avance III 500 MHz spectrometer.…”
Section: Methodsmentioning
confidence: 99%
“…In this work, we report on three chiral aldehyde-catalyzed asymmetric substitution reactions of N-unprotected amino acid esters with aryl halides, [39][40][41][42][43][44] allyl chlorides, and benzyl chlorides. [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] Although the N-functionalization byproducts are not suppressed completely, the de-sired C-functionalization products can be generated in moderate-to-high yields with good-to-excellent enantioselectivities for all three transformations. Furthermore, the arylation product is used for the formal total synthesis of the clinical candidate compound (+)-AG-041R, and three reaction models are proposed based on the results of control experiments and density functional theory (DFT) calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Among organocatalytic methods, phase transfer catalytic (PTC) reactions represent one of the simplest and most efficient tools for enantio-differentiation synthesis [32][33][34][35]. The most commonly used chiral catalysts of natural origin are ammonium salts, derivatives of Cinchona alkaloids, among others, due to their availability and economic considerations [36][37][38][39]. Moreover, it has been repeatedly shown that the use of large substituents on the nitrogen atom of the quinuclidinium ring improves the properties of such a catalyst [40,41].…”
Section: Introductionmentioning
confidence: 99%